Conjugated Polymer Nanoparticle‐Triplet Emitter Hybrids in Aqueous Dispersion: Fabrication and Fluorescence Quenching Behavior. Issue 3 (14th December 2015) - Bandyopadhyay, Sujoy; Métivier, Rémi; Pallavi, Pragyan; Preis, Eduard; Nakatani, Keitaro; Landfester, Katharina; Patra, Abhijit; Scherf, Ullrich
Abstract : Conjugated polymer nanoparticles based on poly[9, 9‐bis(2‐ethylhexyl)fluorene] and poly[ N ‐(2, 4, 6‐trimethylphenyl)‐ N, N ‐diphenylamine)‐4, 4′‐diyl] are fabricated using anionic surfactant sodium dodecylsulphate in water by miniemulsion technique. Average diameters of polyfluorene and polytriarylamine nanoparticles range from 70 to 100 and 100 to 140 nm, respectively. The surface of the nanoparticles is decorated with triplet emitting dye, tris(2, 2′‐bipyridyl)ruthenium(II) chloride. Intriguing photophysics of aqueous dispersions of these hybrid nanoparticles is investigated. Nearly 50% quenching of fluorescence is observed in the case of dye‐coated polyfluorene nanoparticles; excitation energy transfer is found to be the dominant quenching mechanism. On the other hand, nearly complete quenching of emission is noticed in polytriarylamine nanoparticle‐dye hybrids. It is proposed that the excited state electron transfer from the electron‐rich polytriarylamine donor polymer to Ru complex leads to the complete quenching of emission of polytriarylamine nanoparticles. The current study offers promising avenues for developing aqueous solution processed‐electroluminescent devices involving a conjugated polymer nanoparticle host and Ru or Ir‐based triplet emitting dye as the guest. Abstract : Well‐defined conjugated polymer nanoparticles based on polyfluorene and polytriarylamine backbones are fabricated in an aqueous dispersion by the miniemulsion technique. The triplet emitter tris(2, 2′‐bipyridyl)ruthenium(II) chloride has been attached to the surface of the nanoparticles leading to fluorescence quenching in these nanoparticles‐dye hybrids. The underlying excitation energy/charge transfer process from nanoparticles to surface‐bound dyes is probed.